The Effect Of Work Stress On Employee Performance CV. Berta Lestari Anggana - Karunia Auwliya Amin; Fenty Fauziah; Rahman Ansari; Joko Sabtohadi (Sean Institute, 2022)
This study aims to determine the effect of work stress on the performance of CV. Berta Lestari Anggana. This research method uses quantitative research methods. The analytical technique used in this research is descriptive quantitative which aims to determine the influence of the independent variable (X), namely work stress on the dependent variable (Y), namely employee performance. Data collection techniques in this study is to use a questionnaire distributed to all employees of CV. Berta Lestari Anggana. With a total population of 40 employees. The sampling technique was carried out using the saturated sample formula. For the analysis tool in this study using a simple linear regression test, classical assumption test and hypothesis testing. The results in this study are the t test value (3.605) which shows a value greater than the t table value so that partially or t test the work stress variable (X) affects employee performance (Y) at CV. Berta Lestari Aggana.